Role of Molecular Targeted Therapeutic Drugs in Treatment of Oral Squamous Cell Carcinoma: Development and Current Strategies—A Review Article - Singh, Himanshu; Patel, Vedant (Global Medical Genetics, 2022)
Because of active advancement in the field of biomedicine, people have in-depth knowledge of biological nature of malignant tumors and are able to recognized the overexpression of different molecules such as vascular endothelial growth factor receptor, cyclin-dependent kinase, and programmed cell death receptor. Presently, various targeted therapeutic drugs are used in different clinical trials in those patients suffering from oral squamous cell carcinoma. In this review, we converse about the various targeted therapeutic drugs and their advancement in the treatment of oral squamous cell carcinoma. This review scrutinizes the existing documentation in the literature related to the targeted therapies for oral squamous cell carcinoma. English language articles were searched in various databases such as PubMed, Scopus, Science Direct, and Google Scholar. The keywords used for searching are “oral squamous cell carcinoma,” “targeted therapy,” and “therapeutic drugs.”
Keywords: oral squamous cell carcinoma; therapeutic drugs; targeted therapy